2017
DOI: 10.18632/oncotarget.21433
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of adipose-derived mesenchymal stem cells against brain death-induced remote organ damage and post-heart transplant acute rejection

Abstract: We tested the hypothesis that allogenic adipose-derived mesenchymal stem cells (ADMSCs) alleviated brain death (BD)-induced remote organ damage and events of post heart-transplant acute rejection. To determine the impact of BD on remote organ damage, adult-male F344 rats (n=24) were categorized sham-control (SC), BD and BDMSC (allogenic ADMSC/1.2 × 106 cells/derived from F344 by intravenous transfusion 3 h after BD procedure). To determine the protective effect of allogenic ADMSCs, animals (n=8/each group in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 57 publications
(86 reference statements)
22
40
0
Order By: Relevance
“…One important finding in the present study was that intravenous administration of allogenic AMDSC effectively ameliorated BD-caused remote cardiac organ damage. Interestingly, our recent study demonstrated that allogenic ADMSC therapy significantly reduced the incidence of BDinduced post heart-transplanted rejection [37]. Our current findings therefore corroborate those of our recent study [37].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…One important finding in the present study was that intravenous administration of allogenic AMDSC effectively ameliorated BD-caused remote cardiac organ damage. Interestingly, our recent study demonstrated that allogenic ADMSC therapy significantly reduced the incidence of BDinduced post heart-transplanted rejection [37]. Our current findings therefore corroborate those of our recent study [37].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, our recent study demonstrated that allogenic ADMSC therapy significantly reduced the incidence of BDinduced post heart-transplanted rejection [37]. Our current findings therefore corroborate those of our recent study [37]. Another important finding was that ECSW therapy was comparably as effective as ADMSC for alleviating BDcaused remote cardiac damage.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations